Fundamental nuclear structure symmetries in double beta decay processes - Civitarese, O. (HNPS Advances in Nuclear Physics, 2020)
The nuclear structure physics of double beta decay transitions is reviewed starting from the consideration of fundamental symmetries of the nuclear many body problem. The problems found in the use of the Quasiparticle Random Phase Approximation (QRPA) and related approximations, in dealing with the calculation of nuclear double beta decay observables, are understood in terms of the mixing between isospin collective and intrinsic variables.